Use of Folic Acid Supplements in Early Pregnancy in Relation to Maternal Plasma Levels in Week 18 of Pregnancy - Roth, Christine (2012)
We compared plasma-folate at week 18 of gestation with self-reported use of supplements containing folic acid from before pregnancy to 17 weeks gestation. Birth cohorts typically measure plasma-folate in mid-gestation, but effects of folic acid supplementation are sometimes specific to the periconceptional period. The relationship between mid-gestation plasma-folate and periconceptional supplementation is not known. The sample comprised 2911 women from The Norwegian Mother and Child Cohort Study. For women reporting continuous supplementation from gestational week -4-17 (N=238), median plasma-folate was 15.72 at week 18 (in nmol/L). This was about threefold higher than the median plasma-folate of 5.67 for women reporting no supplementation from week -4-17 (N=844), but only slightly higher than the median plasma-folate of 13.34 for all women reporting supplementation in week 13-17 (N=1158). Reported supplementation before week 8 was not associated with plasma-folate at week 18, in an analysis that adjusted for continued supplementation after week 8. Overall we found a strong and coherent relationship between self-reported folic acid use and plasma-folate at week 18. We also found that plasma-folate at week 18 did not reflect self-reported supplementation before 8 weeks. For periconceptional supplementation per se, self-report data may offer a better measure.